2017
DOI: 10.26481/marble.2017.v1.399
|View full text |Cite
|
Sign up to set email alerts
|

Liberty, Equality, Democracy? The supposed relationship between democratic institutions and income inequality

Abstract: The democratic process was always praised for it supposedly reduces inequalities. Indeed, the voice given to citizens in the democratic decision-making process, enables the less favoured part of the population to have the political system addressing their demands. Among them, reducing inequalities inherent to any given system is often to be found in politicians' electoral pledges. The democratisation of an unprecedented number of countries in recent history however, failed to produce expected results in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Good governance has been identified as an important element in increasing income (Kaufmann et al, 2002) and inequality (Shafique et al, 2006;Abd Elalim, 2020) Robinson (2000) found that income inequality declines when governance effectiveness increases. Chong and Calderon (2000) found good governance is only significant for richer countries, Lambert (2017) found no significant relationship, and Huang and Ho (2018) claimed inequality in income distribution is conditional on the economic, ideological and societal conditions of the nation. Hence, there is ample past literature on income inequality but they are either inconclusive or lack coverage of the relationship between the green economy and governance, which this paper aims to examine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Good governance has been identified as an important element in increasing income (Kaufmann et al, 2002) and inequality (Shafique et al, 2006;Abd Elalim, 2020) Robinson (2000) found that income inequality declines when governance effectiveness increases. Chong and Calderon (2000) found good governance is only significant for richer countries, Lambert (2017) found no significant relationship, and Huang and Ho (2018) claimed inequality in income distribution is conditional on the economic, ideological and societal conditions of the nation. Hence, there is ample past literature on income inequality but they are either inconclusive or lack coverage of the relationship between the green economy and governance, which this paper aims to examine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Brazil also experiences extreme income inequality, while China, whose democratic institutions are questionable, faces a much more balanced distribution of income. Given this, it is logical to question whether the notion that "more democracy equals more equality" is correct, or whether there is more than simple causality (Lambert, 2017).…”
Section: Democracy and Equalitymentioning
confidence: 99%